If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n = 5n + -6 Reorder the terms: 4n = -6 + 5n Solving 4n = -6 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. 4n + -5n = -6 + 5n + -5n Combine like terms: 4n + -5n = -1n -1n = -6 + 5n + -5n Combine like terms: 5n + -5n = 0 -1n = -6 + 0 -1n = -6 Divide each side by '-1'. n = 6 Simplifying n = 6
| -68+24=-4x+15x | | 5d+-11=2d+2 | | 2x-1=x-3 | | -7=5n+3 | | 7-7=4x+3x | | 4t-2+t^2=b+t^2 | | 6x+17=71 | | 4(2x-2)=9x | | 2x^2-18x+40= | | 1x+5=-1 | | -9x+9+10x=-7+13 | | 36x+12=60 | | -2b=-5xb-6 | | 5n+3=2n+4-3n | | 4x-7x=30 | | d-3= | | 0.75y-6=0.25y+10 | | b+3=2b-7 | | 5y+4=4y+5 | | 2x-5=23 | | 32-6x=20 | | 2(4n-5)+7n= | | 4x^3+6x^2-18x= | | x^2-30x-64=0 | | 3b-5-7b-6= | | 6x+2=1-x | | -3=5x-2 | | -(5y+2)-(-4y-4)=-5 | | 10-y=2y+3 | | 0=5x-2 | | 18=6-8c | | Y=5(0)-2 |